Seismic Behaviour of Corrosion Damaged Reinforced Concrete Columns Under Combined Loadings - Akbas, Elif Nazlı; Şensoy, Serhan; Eren, Özgür (Springer Science and Business Media Deutschland GmbH, 2024)
The corrosion of reinforcement is a major concern for the structural integrity and durability of reinforced concrete (RC) structures. In order to investigate the effect of reinforcement corrosion on bearing capacity and changes in the collapse mechanism, an experimental study on two identical square columns with a section size of 200 × 200 mm were designed, one column was kept sound and the other one was corroded by applying accelerated corrosion process. The two columns were tested under a constant axial compression and reversed cyclic torsional loading with variable drift amplitudes. In order to calibrate accelerated corrosion process for the columns, the results of preliminary corrosion tests, applied to bare steel bars and later on reinforced concrete beams with a section size of 600 × 150 × 150 mm, were used. The results of the experiment on columns showed that the reinforcement corrosion in concrete structures can cause reduction of the strength and ductility up to 20.54% and 11.34% respectively, and also alters the failure modes from bending failure to a shear-bending mode. This could be a significant concern, particularly for buildings in earthquake-prone areas. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
15th International Congress on Advances in Civil Engineering, ACE 2023 -- 2023-09-06 through 2023-09-08 -- Famagusta -- 312069
Keywords: Accelerated Corrosion; Combined Loadings; Corroded RC Columns; Cyclic Test